2023
DOI: 10.3390/cancers15061763
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 Inhibitors—Overcoming Endocrine Resistance Is the Standard in Patients with Hormone Receptor-Positive Breast Cancer

Abstract: Purpose of review: Tamoxifen and aromatase inhibitors can be considered as some of the first targeted therapies. For the past 30 years, they were the endocrine treatment standard in the advanced and early breast cancer setting. CDK4/6 inhibitors, however, are the first substances in almost two decades to broadly improve the therapeutic landscape of hormone receptor-positive breast cancer patients for the upcoming years. This review is designed to discuss the recent history, current role, future directions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 88 publications
0
5
0
1
Order By: Relevance
“…Several clinical trials with CDK4/6 inhibitors have recently reported median overall survival times around 5 years 6 10 . In this patient population, the time interval after the initial treatment becomes increasingly important, as median PFS times for CDK4/6 inhibitors are around 25 – 28 months 40 . As such, disease management will proceed beyond the first progression.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials with CDK4/6 inhibitors have recently reported median overall survival times around 5 years 6 10 . In this patient population, the time interval after the initial treatment becomes increasingly important, as median PFS times for CDK4/6 inhibitors are around 25 – 28 months 40 . As such, disease management will proceed beyond the first progression.…”
Section: Discussionmentioning
confidence: 99%
“…The better understanding of the precise mechanisms of endocrine signaling pathways has translated into targeted therapies which modify these signaling pathways to achieve tumor control. Several drugs have been tested in clinical trials, including CDK4/6 inhibitors 13 , 14 , the Akt inhibitor capivasertib 15 and the PI3K inhibitor inavolisib 16 , and have been found to improve overall survival (ribociclib and abemaciclib) or have shown very promising trends with regards to overall survival (capivasertib and inavolisib).…”
Section: Expansion Of the Therapeutic Spectrummentioning
confidence: 99%
“…Die Kenntnis der genauen Mechanismen der endokrinen Signalwege wurde gezielt in Therapien umgesetzt, die diese Signalwege im Sinne einer Tumorkontrolle modifizieren. Mit den CDK4/6-Inhibitoren 13 , 14 , dem Akt-Inhibitor Capivasertib 15 und dem PI3K-Inhibitor Inavolisib 16 sind in dem Bereich mehrere Medikamente in klinischen Studien getestet worden, die das Gesamtüberleben verbessern (Ribociclib und Abemaciclib) oder die bereits sehr vielversprechende Trends in Richtung Gesamtüberleben gezeigt haben (Capivasertib und Inavolisib).…”
Section: Die üBerwindung Der Endokrinen Resistenzunclassified
“…The molecular mechanisms of tamoxifen resistance are partially understood and involves ER downregulation, ESR1 mutations, modulation of cell cycle regulators, activation of receptor tyrosine kinases and downstream effectors, and modulation of non-coding RNAs [6][7][8][9][10] . The clinical management of tamoxifen resistance involves the use of other endocrine therapies or CDK4/6 inhibitors 11 . However, resistance to the secondline therapies is also inevitable 12 .…”
Section: Introductionmentioning
confidence: 99%